(5/2)x+3=x+(15/2)

Simple and best practice solution for (5/2)x+3=x+(15/2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5/2)x+3=x+(15/2) equation:


x in (-oo:+oo)

(5/2)*x+3 = x+15/2 // - x+15/2

(5/2)*x-x-(15/2)+3 = 0

(5/2)*x-x-15/2+3 = 0

3/2*x-9/2 = 0 // + 9/2

3/2*x = 9/2 // : 3/2

x = 9/2/3/2

x = 3

x = 3

See similar equations:

| 95/1/8 | | 360/40 | | x(5-9)=67+8x(3+4)+9 | | 24w-8-10w=-2(4-7w) | | 212/40 | | 5x+3x=13 | | 21y=4-6x | | 6x-5.5=42.2 | | 61/8*83/4 | | 20-1/3x=72 | | X^2-10x+16=(x-8)(x+2) | | 6-31/12 | | 60t=65(t-(1/6)) | | 8/9-2/63 | | 2-5x=72 | | z-5z=8z-7-z | | 4/5x=-12 | | 60t=65*(t-1/6) | | 9+4x=73 | | 60t=65(t-1/6) | | 3y+4-y=7+y-2 | | 5(r-8)=-5(r-8) | | 8x-2=8x-x | | 2x=2-9y | | (-3/7)+(-4/7) | | 1/4x-2/4+5/2x+1/6 | | 1/4t+23/8=49/16 | | (16/5)y=4+(1/5)y | | 2-44/4*2 | | (t+1)(t-1)=(t+3)(t-4)+7 | | x-3/13=9/13 | | -7x+3y=8 |

Equations solver categories